SELECTION OF OPTIMAL CONDITIONS FOR LONG-TERM STORAGE OF INSECT CELLS IN LOWTEMPERATURE ENVIRONMENT (Scientific journal of the Fergana State University, 2023)
The article is devoted to the use of insect cell culture for biotechnological purposes. The cell culture is one of the most important areas of the industry. Growing and storing cells is one of the main ways to protect them. Helicopvera zea (cloves) and Trichoplusia (cabbage juice) are designed to replicate insect cells in the laboratory and determine optimal long-term storage methods in low-temperature (cryoconservative) environments. Experiments have proven that using Versailles buffers is the best way. At the same time, cell regeneration was carried out with high productivity.